2014
DOI: 10.1186/s40359-014-0026-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving psychosocial health and employment outcomes for individuals receiving methadone treatment: a realist synthesis of what makes interventions work

Abstract: BackgroundFor over 50 years, methadone has been prescribed to opioid-dependent individuals as a pharmacological approach for alleviating the symptoms of opioid withdrawal. However, individuals prescribed methadone sometimes require additional interventions (e.g., counseling) to further improve their health. This study undertook a realist synthesis of evaluations of interventions aimed at improving the psychosocial and employment outcomes of individuals on methadone treatment, to determine what interventions wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…In contrast, MMT patients are generally more stable, more likely to be employed, and less likely to be using drugs or be engaged in criminal activity when compared to PWIDs that are not engaged in treatment. (Jackson, et al, 2014; Sun, et al, 2015). Several studies also indicate that in order for a health education intervention to be successful, they must be combined with structural level approaches that aim to change the political, economic, social and community context of drug use, and that social determinants of health must be taken into account (Aggleton, 2005; Galea & Vlahov, 2002; Nutbeam, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, MMT patients are generally more stable, more likely to be employed, and less likely to be using drugs or be engaged in criminal activity when compared to PWIDs that are not engaged in treatment. (Jackson, et al, 2014; Sun, et al, 2015). Several studies also indicate that in order for a health education intervention to be successful, they must be combined with structural level approaches that aim to change the political, economic, social and community context of drug use, and that social determinants of health must be taken into account (Aggleton, 2005; Galea & Vlahov, 2002; Nutbeam, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Since employment directly impacts quality of life and treatment engagement (De Maeyer et al, 2011;Jackson et al, 2014), Vietnamese methadone programmes should apply a more patient-friendly dosing schedule to attract and retain service users, especially to accommodate those with traditional eight-to-five work schedules. As M. Harris & Rhodes (2013) argued, 'generous constraints' would be beneficial in improving patients' sense of control, in assisting their self-sufficiency, and in reducing risks.…”
Section: Recommendationsmentioning
confidence: 99%
“…Other realist reviews have identified engagement as an important feature of program success (e.g. [ 18 ]). In the present realist review, two instances were identified where successful program engagement yielded positive outcomes: (a) responsiveness to client socio-economic needs and (b) matching to client lived experience.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that engagement has not previously been noted within COSAP program literature, it has been validated elsewhere. Findings from Jackson and colleagues’ [ 18 ] realist review of methadone treatment programs emphasized the importance of client engagement, specifically within the contexts of client-centred treatment, attention to client SES conditions and positive therapeutic relationships. From a broader perspective, other health care fields such as nursing have also emphasized the importance of patient engagement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation